Novos desafios para o Serviço Social: uma análise sobre o poder disciplinar a partir de Michel Foucault - Pagano, Thaís (2021)
In this research, a dialogue is carried out between Michel Foucault's studies on disciplinary power and the professional practice of the social worker, in order to identify contributions to strengthening a praxis in line with the professional Ethical-Political Project and the valorization of pluralism in the intellectual debate, starting with the idea that this contribution is possible, through the Foucauldian analysis of disciplinary society power exercise, which marks contemporary society. It seeks to understand whether it is possible to identify and absorb, within the professional category, subsidies arising from disciplinary power reflections carried out by Foucault, for a professional practice committed to the interests of the working class, locating a professional practice guided by the use of knowledge-power, so it is possible to think about the resistance that inhabits it, and that it has found in itself a commitment to knowledge linked to the exercise of reflection and questioning. The process guiding this study took place through understanding Michel Foucault's thought, with a brief biography, and a study on power relations in disciplinary society; study of the profession's trajectory, its fundamentals and main contemporary challenges. Questionnaires answered by 15 social workers and 2 teachers of Philosophy were evaluated in order to find out if there is an approximation of the interviewees with Foucault's thinking. The trajectory showed Foucault's reflections on disciplinary power provide important contributions to social worker professional practice, favor pluralism, and enrich intellectual profession debate. The presented elements provide a dialogue between Foucault's study on the relationship between power and Social Service, a profession whose formation, in Brazil, is based on the Marxist tradition, aimed at facing social questions, through the uninterrupted investigation of the capitalist system functioning, as a support for professional intervention. The aim is to provide, to Social Service theoretical field, an expansion of its references, as well as the adoption of new professional practice analytical perspectives. The movement taking place with this thesis is to create a space for interlocution, without apriorism, without resistance, for those who fear being unfaithful to Marxist thought. There is no intention to simplify this challenge and I believe that the task of understanding the divergences, contradictions and similarities between the different theoretical currents has an important complexity